Effect of boron and potassium levels on seed yield and oil quality of sunflower (Helianthus annuus L.): EFFECT OF BORON AND POTASSIUM LEVELS ON SEED YIELD AND OIL QUALITY OF SUNFLOWER - P JYOTHI; T ANJAIAH; I Y L N MURTHY; M RAJESHWAR; S A HUSSAIN (Journal of Oilseeds Research, 2017)
A field experiment was conducted at College farm, College of Agriculture, Rajendranagar during rabi 2016-17 with sunflower hybrid GK 2002 in a factorial randomized block design with 16 treatment combinations comprising of four levels of boron and four levels of potassium viz., B0K0, B0K15, B0K30, B0K60, B0.5K0, B0.5K15, B0.5K30, B0.5K60, B1K0, B1K15, B1K30, B1K60, B1.5K0, B1.5K15, B1.5K30, B1.5K60 to investigate and find out the optimum dosage of boron and potassiumto increase the sunflower seed yield and oil quality. Significantly higher seed yield was obtained withB1.5K60 treatment (1430 kg/ha) followed by B1.5K30 (1419 kg/ha), B1K30 (1410 kg/ha) and B1K60 (1416 kg/ha). However, B1K30 treatment showed economicallybeneficial. Significantly higher oil and protein yields were recorded with B1K30, B1K60, B1.5K30 and B1.5K60. The highest linoleic acid content (75.3 %) was recorded with B1K30 and lowest (71.29 %) with control.